HUBUNGAN WORK-LIFE BALANCE TERHADAP STRES KERJA PEKERJA DI PROYEK BBPPT KOMINFO PT PP (PERSERO) TBK. PADA TAHUN 2022 - Diah Devara Kusumawardani, (2023)
Work stress is stress that is related to the workplace environment which is about pressure and responsibility that have an impact on a person's psychology. One of the factors that can cause work stress is a poor work-life balance. This study aims to determine the relationship between work-life balance and other variables such as age, education level, marital status, and work income with work stress at Proyek BBPPT PT PP (Persero) Tbk. This study is a quantitative study using a cross-sectional design with chi-square test analysis on a total population of as many as 100 people. The research instrument uses The Workplace Stress Scale (WSS) questionnaire and the work-life balance questionnaire by Fisher, Bulger, and Smith. The results showed there was no relationship between work-life balance (p=0.242), age (p=0.577), an education level (p=0.439), marital status (p=1.000), and work income (p=0.468) with work stress. It can be concluded that there are no variables related to work stress. Nevertheless, companies can provide psychological counseling services for workers to maintain their mental health.